The Role of the University In developing awareness of Social responsibility among its employees under the Circumstances of the Corona pandemic – A Field study in the community colleges at King Khalid University – - Ibrahim, Reda Abdelfattah (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to present the actual responsibility of the King Khalid University toward the community as well as its employees during the Corona pandemic. The study applied the descriptive analytical approach to achieve this aim. The main data of this study have been collected using a questionnaire which distributed between samples from King Khalid University ‘s employees. The collected data have been processed using the statistical analysis program (SPSS) which handle the input, processing and testing the study hypotheses. The study sample reached (106) single, and the study seeks to answer the main question, which is: how far the university’s commitment of social responsibility towards its employees during the circumstances of the Corona pandemic? The results assured the presence of a statistically significant relationship to the university’s role in developing the employee’s awareness of the social responsibility towards the community during the circumstances of the Corona pandemic. Accordingly, the study recommended the necessity of establishing an independent department within the university for social responsibility and reporting to the higher management directly. The main mission of this department will be limited to designing and implementing volunteer programs as well as the coordination. Finally, the study confirmed the activation of cooperation between the university and civil society institutions to adopt community initiatives and ensure their sustainability.
Keywords: university; social responsibility; corona pandemic